Akurasi Bantuan Stimulan Perumahan Swadaya (BSPS) terhadap RTLH Menggunakan Metode Weighted Product - Apriliana, Milla (SAFE-Network, 2021)
Help Stimulant Self-help Housing (BSPS) is a program of the Ministry of Public works and Housing organized by the government. Agam Regency is one of the regions that obtain the BSPS since the year 2016, with a fairly large number. In the determination of the non-BSPS-party districts still take the decision in a subjective manner, so that fact shows that there are many underprivileged communities that are not listed as one of the recipients of the program. This research is conducted to assist Decision-Making in determining the Accuracy of the acceptance program of BSPS against the House is Not Livable (RTLH) so right on target with the help of the implementation of the system using the method of Weighted Product. The method of Weighted Product using the technique of multiplication to connect the rating attribute, then the rating attribute to the power with the weight of attributes is concerned, the weights and the criteria are adjusted to the terms that have been assigned to the Office of Housing and residential areas in Agam Regency. There are 10 main criteria and 20 test data that will be if in doing the calculations. The results of data processing gives the value of the weight on each criteria and then performed the ranking to get the help of a Decent Home. The implementation of this system-based website by using PHP programming language and MySQL as the database. The results of the testing of this method obtained the highest score that is 0.059 of an alternative to the 19 which is Junaidi. Then do a comparison with manual calculation with the system that made and get the same results with 100% accuracy rate and is expressed accurately. A Decision Support system that can be applied to determine priority recipients of the program BSPS obtained from the results of the accuracy of the data and thus can assist the District in making decisions accurately and objectively.